Ralationship between polymorphisms and diplotypes of HLA-G 3’UTR and fetuses with abnormal chromosomes or unexplained pregnancy loss (UPL) - Danping Xu; Yiyang Zhu; Jun Wang; Heqin Guan; Xiuzhen Shen (Human Genomics, 2024)
Abstract Objectives Human leukocyte antigen G (HLA-G) plays a crucial role in pregnancy. Pregnancy loss (PL) is caused by a variety of causes, such as fetal chromosomal abnormalities, maternal hypertension and diabetes, immune causes, spontaneous immune diseases, infections, unknown causes, etc. This study reports on the association of fetal HLA-G 3’UTR polymorphisms and diplotypes with chromosomally abnormal fetuses (CAF) or unexplained pregnancy loss (UPL). Methods A total of 552 specimens were collected and grouped by next-generation sequencing technology (NGS) and fetal survival: UPL (112 cases), CAF (170 cases) and control (258 cases). The polymorphisms of HLA-G 3’UTR in all samples were detected by Sanger sequencing. The genotypes, haplotypes and diplotypes of HLA-G 3’UTR were analyzed. The classification and regression tree (CART) analysis was used to evaluate the role of HLA-G diplotypes in predicting fetal outcomes. The correlations between CAF or UPL and maternal age, paternal age, times of miscarrage, times of delivery were analyzed by logistic regression. Results The frequencies of HLA-G + 2960del/del and + 3035CC genotypes were remarkablly increased in CAF than those in control group. The frequencies of HLA-G + 2960ins/del, + 3010CC, + 3035TC, + 3142GG, + 3187AA in CAF were significantly lower than those in normal fetuses. Through genetic models and logistic regression analysis, the dominant model of HLA-G 3’UTR genotypes [such as + 2960 (OR = 1.27, 95% CI = 1.05–1.54, p = 0.016), + 3010 (OR = 0.78, 95% CI = 0.63–0.97, p = 0.026), + 3035 (OR = 1.22, 95% CI = 1.00–1.49, p = 0.047), + 3142 (OR = 0.76, 95% CI = 0.62–0.95, p = 0.014) and + 3187 (OR = 0.80, 95% CI = 0.65–0.99, p = 0.041)] were dramatically associated with CAF. However, the frequencies of HLA-G + 3010GC, + 3142GC and + 3187AG in fetuses with UPL were memorably decreased than those in normal fetuses. No significant difference was found in the frequencies of HLA-G haplotypes in all groups. However, the frequency of UTR-1 positive specimens in CAF was significantly higher than that in UPL and control group. At the same time, the frequency of UTR-1/UTR-3 diplotypes in CAF was observably higher than that in UPL and control group, while the UTR-1/UTR-7 frequency in UPL was signally lower than that in control group. Multivariate logistic regression analysis indicated that positive HLA-G UTR-1 (OR = 1.8, 95% CI = 1.16–2.81, p = 0.009), times of abortion (OR = 1.23, 95% CI = 1.02–1.50, p = 0.035), and times of delivery (OR = 0.31, 95% CI = 0.20–0.48, p < 0.001) were correlated with CAF. Conclusions This study suggests that HLA-G 3’UTR polymorphisms and diplotypes play an important role in the process of successful pregnancy of the embryos with abnormal chromosomes after fertilization. At the same time, Different alleles or diplotypes also affect the development of embryos with UPL.